2018
DOI: 10.5194/acp-18-2119-2018
|View full text |Cite
|
Sign up to set email alerts
|

Optical and microphysical properties of natural mineral dust and anthropogenic soil dust near dust source regions over northwestern China

Abstract: Abstract. Mineral dust aerosols (MDs) not only influence the climate by scattering and absorbing solar radiation but also modify cloud properties and change the ecosystem. From 3 April to 16 May 2014, a ground-based mobile laboratory was deployed to measure the optical and microphysical properties of MDs near dust source regions in Wuwei, Zhangye, and Dunhuang (in chronological order) along the Hexi Corridor over northwestern China. Throughout this dust campaign, the hourly averaged (±standard deviation) aeros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 94 publications
(101 reference statements)
1
20
0
Order By: Relevance
“…The source of atmospheric aerosol is complicated. For example, in the studying area in Northeastern China, the AOD can be significantly affected by mineral dust from the upstream Gobi and Taklimakan desert (Li et al, ; Wang, Liu, et al, ; Wang, Wen, et al, ), and in that case, AOD has no correlations with trace gases. Therefore, the good correlation shown in Figure indicated that those pollutants were mainly emitted from the fire and transported downwind.…”
Section: Resultsmentioning
confidence: 99%
“…The source of atmospheric aerosol is complicated. For example, in the studying area in Northeastern China, the AOD can be significantly affected by mineral dust from the upstream Gobi and Taklimakan desert (Li et al, ; Wang, Liu, et al, ; Wang, Wen, et al, ), and in that case, AOD has no correlations with trace gases. Therefore, the good correlation shown in Figure indicated that those pollutants were mainly emitted from the fire and transported downwind.…”
Section: Resultsmentioning
confidence: 99%
“…In Japan, the concentrations of bacterial cells and the structure of airborne bacterial communities in the near-surface air and the free troposphere are affected by Asian dust events (Maki et al, 2014(Maki et al, , 2015. Similarly, the yellow sandstorms that originate in Asian deserts have been reported to affect the ambient air quality of Taiwan by increasing the levels of fungal spores (Ho et al, 2005;Wu et al, 2004). Results from South Korea also show that Asian dust impacts both airborne fungal concentrations and fungal communities (Jeon et al, 2011(Jeon et al, , 2013Yeo and Kim, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the concentrations of bacterial cells and the structure of airborne bacterial communities in the near-surface air and the free troposphere are affected by Asian dust events . Similarly, the yellow sandstorms that originate in Asian deserts have been reported to affect the ambient air quality of Taiwan by increasing the levels of fungal spores (Ho et al, 2005;Wu et al, 2004). Results from South Korea also show that Asian dust impacts both airborne fungal concentrations and fungal communities (Jeon et al, 2011(Jeon et al, , 2013Yeo and Kim, 2002).…”
mentioning
confidence: 95%